Radiocarbon Dating of Lacustrine Strands in Arctic Alaska - Carson, Charles E. (ARCTIC, 1968)
Reports on 1958-64 studies of lacustrine processes and basin sequences in the Pt Barrow region. Lakes developed in the ice-rich late Pleistocene Gubik Formation are surrounded by two to four exposed and revegetated wave-cut shelves which suggest regional correlative cycles of piracy due to minor shifts in climate and eustatic level. Shelves exposed when lakes are intersected by tundra streams and drained, require 10-20 yr for revegetation in the present climate. Radiocarbon dates of samples from abandoned strands show the majority to be <3500 yr old. The postglacial transgressive-regressive lacustrine cycle is described and diagrammed. The lacustrine maximum transgression probably occured near the end of the hypsithermal (3500-4000 BP) and the onset of the post-hypsithermal cooling phase was synchronous with the initial period of draining. More systematic investigation is required however, before clear time correlation of geomorphic surfaces and events can be established. Radiodatations de plages soulevées dans l'Alaska arctique. C'est par capture et drainage que les cours d'eau de la toundra provoquent l'apparition des banquettes lacustres actuelles, à 10-12 milles (16-19,3 km) à l'intérieur de la côte arctique de l'Alaska. Près de Point Barrow, ces surfaces demandent, sous le climat actuel, de 10 à 20 ans pour se recouvrir de végétation. Les nombreux lacs-reliques de la région sont entourés par une séquence stabilisée de deux à quatre plages soulevées, ce qui suggère qu'aux époques précédentes, le phénomène de la capture régionale a pu être plus fréquent.Les trente échantillons radiodatés indiquent que la majorité des plages soulevées ont moins de 2500 ans; mais avec un nombre aussi limité de datations, ni les nivaux équivalents ni les séquences similaires ne peuvent indiquer une corrélation chronologique claire. Cependant, ces données suggèrent que l'expansion lacustre a atteint un maximum vers la fin de l'hypsithermal – environ 2500-4000 ans av.p. – et que le début de la phase de refroidissement ...